KONSTRIBUSI MASYARAKAT DALAM MITIGASI DAN ADAPTASI MASA PANDEMI COVID-19 DI KABUPATEN BUTON UTARA - Ari Sartinah; Dian Munasari Solo (Jurnal Pengabdian NUSANTARA, 2021)
This service aims to provide education to the public about the dangers and ways of preventing Covid-19. The location of the Thematic Real Work Lecture (KKN) activity is the community in Kulisusu Village, Loji Village, North Buton Regency. Thematic KKN Service Methods through student involvement in implementing five Work Programs namely Healthy Living Community Movement (Germas), Clean and Healthy Living Behavior (PHBS), Community Movement Using Masks (Gemas), Family Medicinal Plants (TOGA) and Making Antiseptics and Disinfectants. The results of this Community Service through Thematic KKN Activity have succeeded in providing education and understanding of the prevention and transmission of Covid-19 by implementing Clean and Healthy Living Behaviors (PHBS) in the surrounding environment, how to use good masks, how to make and use antiseptics and disinfectants and use of medicinal plants which has properties as a prevention of covid-19.